Murid Pri dan Nonpri pada Sekolah Pembauran: Kebijakan Asimilasi Orde Baru di Bidang Pendidikan dan Dampaknya terhadap Masyarakat Multikultural - Usman Pelly (Antropologi Indonesia, 2003)
This paper is written based on the author's research on the policy of Chinese assimilation in two types of high school in Medan (1985-1986). Based on education policy issued in 1975,Indonesian students of Chinese descent are brought to contact with 'local students' to absorb so-called National culture through assimilation in schools. The author specifies two models of assimilation school, one is public schools, and the other is private schools with certain religious affiliations. There are seven indicators to measure successful assimilation (cultural, structural, amalgamations, identification, attitude, behaviour, and civic education) which show that the overall success of the assimilation agenda is still open to question if not unexpected. However, the author remarks that surprisingly, the assimilation process seems to have met with greater success in religious schools rather than public schools and he also critically points out that the basic assumption of assimilation is misleading and does not support the enrichment of a multicultural society.